Strengthening Human Capital Department Roles through Building Collaboration with External Stakeholders - Khristiningrum, Veronica Afridita; Gustomo, Aurik; Ginting, Henndy (School of Business and Management Institut Teknologi Bandung, 2021)
Human capital department is found to have important roles in supporting the business objectives of a company. High competition in the customer goods industry makes the company strengthen its human capital department role because the human capital department becomes a strategic business partner. Most companies enhance their human capital departments internally, but internal resources have limitations in developing human capital department roles. The human capital department needs to look further to external resources that could support their roles. To strengthen human capital department roles through collaboration with external stakeholders needs further examination. This paper aimed to explore the external stakeholders in strengthening human capital department roles in consumer goods companies. Based on qualitative, semi-structured interviews of human capital leaders from five consumer goods companies in Indonesia, we identify six stakeholders based on the human capital department activities leading to human capital department roles. The external factors include outsourcing, vendors, government, business and professional associations, community, and university. Collaboration with these stakeholders strengthen the human capital department roles of consumer goods company.